Sustainability of rice-wheat cropping system through natural resource management in Haryana - Poswal, Randhir Singh; Singh, Randhir; Hansra, Baljit Singh (Journal of Cereal Research, 2025)
The present study was undertaken in Haryana State (North India) in rice (Oryza sativa L)-wheat (Triticum aestivum L) cropping system. Four rice-wheat growing districts i.e. Karnal Kurukshetra, Kaithal and Ambala were selected for the study. From each district two blocks and from each block two villages were selected randomly. From each village 20 farmers were selected by using stratified random sampling technique, thus constituting a sample size of 160 farmers. Data were collected by using personal interview method during 2011 from the small, medium and large categories of the farmers on the basis of land holding size. Results indicated that the mean monthly maximum temperature of about 210C and minimum temperature of 6.50C in the months of December, January and February produced the optimum grain yield of wheat (4.68 t ha-1). The probability of receiving high intensity rainfall was found to be increased in the month of September which affects the yield of rice crop adversely. Majority of the farmers responded that deep groundwater table provides good quality of irrigation water. The results further indicated that 82.5% respondents were applying appropriate number and depth of irrigation water and 70.62 % farmers were using minimum tillage. About 61 % farmers were incorporate crop residue in the crop field. About 49 % farmers adopted zero-tillage/direct seeding for sowing of wheat as well as rice crop, whereas 33.12 % farmers grow green manuring (Sesbania/green gram) before transplanting of rice crop. Rice-wheat cropping system was found to be stable in terms of its yield potential as indicated by a higher sustainability yield index of rice (0.78) and wheat (0.80). The farmers’ observation inferred that the resource conservation technologies have the potential to decrease the cultivation costs and making rice-wheat cropping system more resource-use-efficient, profitable and sustainable.